SENGKETA KONSUMEN DAN TEKNIS PENYELESAIANNYA PADA BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) - Bustamar Bustamar (Institut Agama Islam Negeri Batusangkar, 2016)
The use of products on goods and services by customer potentially creates conflicts due to material lost suffered by the customers as the result of using particular products. The Acts Number 8 Year 1999 of Customers Protection provides customer with a right to work out any conflicts by consulting a costumer’s conflict resolution board (BPSK). The resolution of the conflicts is achieved through such processes as mediations, conciliations and arbitration which involve three elements: government, businessmen, and customers. All verdicts made by BPSK in the form of mediation and are final and legal. However, the arbitration ones are possible to be proceeded to the trials.Kata kunci: sengketa, konsumen, BPSK